Estrous synchronization and scheduled artificial insemination for gilts - Duane L Davis; Jeffrey S Stevenson; W E Schmidt (Kansas Agricultural Experiment Station Research Reports, 1983)
Gilts were artificially inseminated on the fifth, sixth and seventh days after estrous synchronization with altrenogest (scheduled AI). Contemporary controls also were synchronized but were checked for estrus twice daily. Scheduled AI gilts had farrowing rates and litter sizes similar to controls. Altrenogest is not presently available to pork producers but these results suggest that it could be used in combination with artificial insemination to schedule breeding according to a predetermined schedule.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Estrous synchronization; Artificial insemination; Gilts